Authenticity and Historicity of The Quran from The Perspective Of H. Abdul Malik Karim Amrullah (Buya Hamka) - Waharjani; Mohammad Jailani (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
The Quran holds a central position in the lives of Muslims, particularly as a source of worship through recitation, memorization, and understanding of its teachings. However, studies on the historicity and authenticity of the Quran have received limited attention from the Muslim community at large.However, this issue cannot be overlooked, as Orientalists, through their research, attempt to obscure and even distort facts about the Quran's historicity and authenticity.Therefore, this research aims to present perspectives on the historicity and authenticity of the Quran based on factual evidence from the Quran and the Hadith of Prophet Muhammad (SAW), from the perspective of Buya Hamka. This study employs a qualitative approach, drawing from relevant books or journals on the theme, which are then summarized and analyzed to provide new insights that complement existing research. Based on the gathered data, the history of the Quran, both in terms of its revelation and its textual preservation, confirms that the Quran is the divine revelation received by Prophet Muhammad (SAW), either directly or through the intermediary of Angel Gabriel. Meanwhile, the authenticity of the Quran remains well-maintained, starting from its initial reception of revelation memorized by the Prophet and his companions, a tradition that continues to this day with many people memorizing the Quran. This research underscores the importance of understanding the historicity and authenticity of the Quran to address misinterpretations and distortions propagated by certain ideologies or perspectives within Islam. The findings of this study reinforce that the Quran is the unchanged revelation of Allah and continues to be an irreplaceable source of guidance for mankind throughout the ages.